Integrated all‐optical switch with 10 ps time resolution enabled by ALD. Issue 3 (9th March 2016) - Moille, Gregory; Combrié, Sylvain; Morgenroth, Laurence; Lehoucq, Gaëlle; Neuilly, François; Hu, Bowen; Decoster, Didier; de Rossi, Alfredo
Abstract : The encapsulation of GaAs photonic crystal coupled cavities with an Al2 O3 layer using ALD results in an optimized carrier lifetime of about 10 ps and suppresses the photo‐induced oxidation. This allows all‐optical signal processing up to 5 GHz. The device responds to a sequence of closely spaced pump pulses demonstrating a gating window close to 10 ps, with a contrast as high as 7 dB. Abstract : Abstract The potential of GaAs‐based photonic crystals for fast all‐optical switching in the telecom spectral range is exploited by controlling the surface recombination and, thereby, the carrier relaxation dynamics. The structure is entirely coated with a layer of aluminium oxide using atomic layer deposition. This results in a carrier lifetime of about 10 ps, as determined by spectrally resolved pump–probe measurements. We show that the nonlinear response of the resonator is optimized when it is excited with a few‐picoseconds pulse. This dynamics is perfectly captured by our model accounting for the carrier diffusion with an impulse response function. Moreover, the suppression of photo‐induced oxidation is revealed to be crucial to demonstrate all‐optical operation at GHz rates with average coupled pump power of 0.5 mW (hence 100 fJ/bit). The switching window is 12 ps wide (1/e), as resolved by homodyne pump–probe measurements. The devices respond to a sequence of closely spaced pump pulses demonstrating a gating window close to 10 ps, with a contrast as high as 7 dB.